MINERALISASI NITROGEN DI BAWAH TEGAKAN HUTAN Eucalyptus pellita DAN Acacia mangium Di SUMATERA SELATAN - , LA ODE RUSTAM; , Prof. Dr. Ir. Bambang Hendro Sunarminto, SU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
N mineralization is a change in the form of organic compounds to inorganic bonding. The organic form of nitrogen is very important because it is a form that can be absorbed by plants for their growth and production. The different types of forest stands between E. pellita and A. mangium can affect N mineralization rate. The aim of this study: to measure inorganic mineralization (NH4 + and NO3 -) and compared the levels of ammonium, nitrate and N mineralization under forest stands of E. pellita and A. mangium. And also to study the mineralization process under forest stands of E. pellita and A. mangium. The research was conducted in the field and in the laboratory from February to July 2013. The observation and soil sampling was conducted under forest stands A. mangium and E. pellita in the three different locations namely Banding Anyar, Gemawang and Suban Jeriji at the location PT. Musi Hutan Persada, South Sumatra. Incubation activities and soil analysis carried out at the Laboratory of Soil Science, Agriculture Faculty, Gadjah Mada University. The research uses complete randomized block design consisting of two treatment types of forest stands and 3 replications so that it result 6 treatment. The result shows that the soil under the stand of A. mangium has higher soil moisture content, organic matter, N content, available N content, organic C and N total, while the C/N ratio is lower. The soil under the stand E. pellita has higher pH and clay particle. The hisghest level of ammonium, nitrate and N mineralization are under the stand of A. mangium compared under stand forest of E. pellita. The mineralization in the research location either under the stand of E. pellita or A. mangium is included in nitrification process.